LEGAL POLITICS OF THE BAN ON SAME-SEX MARRIAGE IN INDONESIA FROM A HUMAN RIGHTS PERSPECTIVE - HENDRA LUKITA (Proceeding International Conference on Social Sciences, 2026)
Legal policy is closely related to human rights (hereinafter referred to as HAM). Legal policy is the state's policy to create and enforce laws on human rights. Human rights are the fundamental rights inherent to every individual that require legal protection. A progressive and responsive legal policy is crucial for creating an effective legal system that protects human rights, addresses past violations, and prevents future violations. Legal policy is a policy or strategy for realizing state goals through the creation, implementation, and enforcement of laws . Legal policy determines the direction, form, and content of laws, making them a tool for achieving social goals and national ideals. The purpose of establishing the Unitary State of the Republic of Indonesia is to protect all Indonesian people and all Indonesian territory, advance general welfare, improve the life of the nation, and participate in implementing world order based on independence, eternal peace, and social justice. The rights of Indonesian citizens are regulated in the 1945 Constitution of the Republic of Indonesia (UUD 1945), specifically in articles 27 to 34. These rights cover various aspects of life, including the right to work and a decent living, the right to life, the right to collective selfdevelopment,the right to legal protection ,the right to religious freedom,the right to education,and other rights such as the right to participate in government, the right to vote and be elected in general elections,and the right to social security.